Endoscopic surveillance of head and neck cancer in patients with esophageal squamous cell carcinoma - Kato, Minoru; Ishihara, Ryu; Hamada, Kenta; Tonai, Yusuke; Yamasaki, Yasushi; Matsuura, Noriko; Kanesaka, Takashi; Yamamoto, Sachiko; Akasaka, Tomofumi; Hanaoka, Noboru; Takeuchi, Yoji; Higashino, Koji; Uedo, Noriya; Iishi, Hiroyasu (Endoscopy International Open, 2016)
Background and study aims: Multiple squamous cell carcinomas (SCCs) frequently arise in the upper aerodigestive tract, referred to as the field cancerization phenomenon. The aim of this study was to elucidate the detailed clinical features of second primary head and neck (H&N) SCCs arising in patients with esophageal SCC.Patients and methods: A total of 818 patients underwent endoscopic resection for superficial esophageal cancer between January 2006 and December 2013. Of these, 439 patients met our inclusion criteria, and we retrospectively investigated the incidence, primary sites, and stages of second primary H&N SCCs in these patients.Results: A total of 53 metachronous H&N SCCs developed in 40 patients after a median follow-up period of 46 months (range 9 – 109). The cumulative incidence rates of metachronous H&N SCCs at 3, 5, and 7 years were 5.3 %, 9.7 %, and 17.2 %, respectively. These lesions were frequently located at pyriform sinus or in the posterior wall of the pharynx (70 %, 37/53 lesions). Most of the lesions were detected at an early stage, though 4 lesions were associated with lymph node metastasis when their primary sites were detected (1 postcricoid area, 2 posterior wall of hypopharynx, and 1 lateral wall of oropharynx).Conclusions: Patients with esophageal SCC should undergo careful inspection of the pyriform sinus and posterior wall of the pharynx for detection of H&N SCCs. Methods to open the hypopharyngeal space, such as the Valsalva maneuver, should be included in the surveillance program.